Pertumbuhan fragmen bibit ukuran berbeda dalam pembudidayaan karang hias Acropora formosa - Sinipirang, Frischa A.; Ngangi, Edwin L.A.; Mudeng, Joppy D. (Universitas Sam Ratulangi, 2016)
The objective of research was to evaluate the length and diameter of coral Acropora formosa cultivated with different seed size in Talengen Bay, Tabukan District, Sangihe Island Regency. Data were collected from May to June 2016. Experimental design used was Complete Randomized Design with three treatments, each with three replications. Size of seed as treatment consisted of A: 5 cm, B: 7 cm and C: 10 cm. The experiment was conducted using bench system measuring 60 x 60 cm2, while coral seed was A. formosa. The seed was gathered from the nature around research location. Growth data and water quality parameters were measured every two weeks . Research results showed that the highest absolute length growth was achieved in treatment A (average: 0.70 cm), followed by treatment C (average 0.46 cm) and the lowest was in treatment B (average 0.45 cm). The highest growth of coral diameter was observed in treatment A (average 0.05 cm) and followed by treatment C (average 0.03 cm) and treatment B (0.03 cm). Statistical analysis showed that absolute length growth and coral diameter were not significant. A. formosa cultured with different seed length in Talengen Bay had good growth in which the growth in length was faster than the growth in diameter. Keywords : Acropora Formosa. Absolute growth, Talengen Bay